The Credit Card Knowledge, Financial Self-Efficacy, Credit Card Misuse and Intention to Reuse Credit Card among adults in Pontianak - Wibowo, Pandu B102415012 (Jurnal Manajemen Update, 2019)
The purpose of this paper is to investigate the impact of credit card knowledge and financial self-efficacy toward credit card misuse and intention to reuse credit card. The technological breakthroughs and regulatory reforms of the past decades have brought payment media to the forefront of business, social and political interest. This research is a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. The questionnaire is distributed to 100 sample who fulfill the requirements. The sample of this research are adults in Pontianak that are at least 21 years old. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypothesis of the research is H1 : Credit card knowledge have significant influence on credit card misuse, H2: Financial self-efficacy have significant influence on credit cards misuse, H3: Credit card knowledge have significant influence on intention to reuse credit cards, H4: Financial self-efficacy have signficant influence on intention to reuse credit cards, H5: Credit card misuse have significant influence on intention to reuse credit cards. The result of this research shows that H1, H4 and H5 are accepted but H2 and H3 are rejected.References A, F. (1984). “Many sides of the coin: The psychology of money usage. Personality and Individual Differences. 501-509.Ackert, L., & Church, B. (2015). Credit cards, financial responsibility, and college students: an experimental study. International Journal of Behavioural Accounting and Finance, Vol. 5 No. 1, 1-26.Aghazadeh, H., & Esfidani, M. R. (2007). Internet Marketing Strategies. Iranian Economic Review, 180-191.Allgood, S., & Walstad, W. (2013). Financial literacy and credit card behaviors: a cross-sectional analysis by age. Numeracy, Vol. 6 No. 2, 1-26.Allgood, S., & Walstad, W. (2016). The effects of perceived and actual financial knowledge on credit card behavior. Economic Inquiry, Vol. 54 No. 1, 675-697.Amromin, G., & S., C. (2007). Debit Card and Cash Usage: A Cross-country Analysis. Working Paper, Federal Reserve Bank of Chicago, Number 2007-04.Austin, M. J., & Phillips, M. R. (2001). Educating students: an ethics responsibility of credit card companies. Journal of Services Marketing, Vol. 15 No. 7, 516-528.Awanis, S., & Chi Cui, C. (2014). Consumer susceptibility to credit card misuse and indebtedness. Asia Pacific Journal of Marketing and Logistics Vol. 26 No. 3, 408-429.Bandura, A. (1977). Social Learning Theory. General Learning Press, New York, NY.BBC. (2011, March 2). Credit cards do not count as spending, say young adults. Retrieved from BBC: https://www.bbc.com/news/education-12627107BI. (2012). Surat Edaran Bank Indonesia Nomor 14/17/DASP perihal Perubahan atas Surat Edaran Bank Indonesia Nomor 11/10/DASP perihal Penyelenggaraan Kegiatan Alat Pembayaran dengan Menggunakan Kartu. Retrieved from Bank Indonesia: https://www.bi.go.id/id/peraturan/sistem-pembayaran/pages/se_141712.aspxBorden, L., Lee, S., Serido, J., & Collins, D. (2008). Changing college students’ financial knowledge,attitudes, and behavior through seminar participation. Journal of Family and Economic Issues Vol. 29 No. 1, 23-40.Borzekowski, R, R., E., K., & S., A. (2008). Consumers’ Use of Debit Cards: Patterns, Preferences and Price Response. Journal of Money, Credit and Banking, 40, 149-72.Braunsberger, K., Lucas, L. A., & Roach, D. (2004). The effectiveness of credit-card regulation for vulnerable consumers. . Journal of Service Marketing, 18(5), , 358–370.Braunsberger, K., Lucas, L., & Roach, D. (2004). The effectiveness of credit-card regulation for vulnerable consumers. Journal of Services Marketing, Vol. 18 No. 5, 358-370.Braunstein, S., & Welch, C. (2002). Financial literacy: an overview of practice, research, and policy. Federal Reserve Bulletin, 445-457.Brown, S. P., & Stayman, D. M. (1992). Antecedents and Consequences of Attitude toward the Ad: a Meta-analysis. Journal of Consumer Research, 34-51.Burton, D. (2008). Credit and Consumer Society. Routledge, Oxon.Burton, D., Knights, S., Leyshon, A., Alferoff, C., & Signoretta, P. (2004). Making a market: the UK retail financial services industry and the rise of the complex sub-prime credit market. Competition & Change, Maney Publishing, Vol. 8 No. 1, 3-25.Carlson, N. e. (2007). Psychology: The Science of Behaviour 4th Canadian Edition. Toronto: Pearson Education Canada.Carow, K., & M., S. (1999). Debit, Credit, and Cash: Survey Evidence on Gasoline Purchases. Journal of Economics and Business, 51, 409-422.Chakravorti, S. (2004). Why has Stored-value Card not Caught on? Journal of Financial Transformation, 12: 39-48.Churchill, G. A., & Moschis, G. P. (1979). Television and interpersonal influences on adolescent consumer learning. Journal of Consumer Research, Vol. 6 No. 1, 23-35.Corley, J. K., Jourdan, Z., & Ingram, W. R. (2013). Internet marketing: a content analysis of the research. Electronic Markets.Dafler, F. (2013, April 23). Terindah. Retrieved from Memahami dan Mempelajari SmartPLS: http://feroniadafler.blogspot.co.id/2013/04/mempelajari-dan-memahami-smartpls.htmlDraut, T., & Silva, J. (2004). Generation Broke : The Growth of Debt Among Young Americans. De-mos: A Network for Ideas & Action.Durkin, T. A. (2000). Credit Cards: Use and Consumer Attitudes,1970-2000. Federal Reserve Bulletin.Evans, D., & R. , S. (2005). Paying with Plastic (Second Edition). MIT Press:Cambridge, MA. .Feinberg, R. (1986). Cards as spending facilitating stimuli: a conditioning interpretation. Journal of Consumer Research, Vol. 13 No. 3, 348-358.Fisher, J., Fisher, W., Amico, K., & Harman, J. (2006). An information-motivation-behavioral skills model of adherence to antiretroviral therapy. Health Psychology Vol.25 No.4, 462-473.Fogel, J., & Schneider, M. (2011). Credit card use: disposable income and employment status. YOUNG CONSUMER, 5-14.Foscht, T., Maloles, C., & Chia, S. L. (2010). Debit and credit card usage and satisfaction: who uses which and why – evidence from Austria. . International Journal of Bank Marketing, 28(2), 150-165.Gourville, J., & Soman, D. (1998). Payment depreciation: the behavioral effects of temporally separating payments from consumption. , Journal of Consumer Research, Vol. 25 No. 2, 160-174.Hancock, A., Jorgensen, B., & Swanson, M. (2013). College students and credit card use: the role of parents, work experience, financial knowledge, and credit card attitudes. Journal of Family and Economic Issues, Vol. 34 No. 4, 369-381.Heffner, C. L. (2016). Test Validity and Reliability. Retrieved from AllPsych: http://allpsych.com/researchmethods/validityreliability/Henry. (2011, August 24). Path Analysis with LISREL (Chapter 1). Retrieved from Teori Online: https://teorionline.wordpress.com/2011/08/24/path-analysis-with-lisrel-chapter-1/Henry, P., Garbarino, E., & Voola, R. (2013). Metacognitions about consumer protection and individual responsibility in the credit card domain. Journal of Public Policy & Marketing, Vol. 32 No. 1, 32-44.Hox, J. J., & Bechger, T. (2011). An Introduction to Structural Equation Modeling. Family Science Review, 354-373.Humphrey, D. (2004). “Replacement of Cash by Cards in U.S. Consumer Payments,". Journal of Economics and Business Volume 56, 211-225.Humphrey, D., M., K., & B., V. (2001). Realizing the Gains from Electronic Payments: Costs, Pricing, and Payment Choice. Journal of Money, Credit and Banking, 33, 216-234.Hunt, R. (2003). An Introduction to the Economics of Payment Card Networks. Review of Network Economics Volume 2, 80-96.HYYTINEN , A., & TAKALO, T. (2009). Consumer Awareness and the Use of Payment Media: Evidence from Young Finnish Consumers. Review of Network Economics Vol.8, Issue 2 – June.I, A. (1988). Attitudes, personaliQ, and behaviour. Dorsey.Joo, S., Grable, J., & Bagwell, D. (2003). Credit card attitudes and behaviors of college students. College Student Journal, Vol. 37 No. 3, 405-19.Kapferer, J. N. (2004). The New Strategic Brand Management: Creating and Sustaining Brand Equity Long Term. London: Kogan Page.Klee, E. (2006a). Families’ Use of Payment Instruments During a Decade of Change in the U.S. Payment System. Finance and Economics Discussion Series, Number 2006-01 Board of Governors of the Federal Reserve System. .Komariah, A., & Satori, D. (2010). Metodologi Penelitian Kualitatif. Bandung: Alfabeta.Lachance, M., Beaudoin, P., & Robitaille, J. (2006). Quebec young adults’ use of and knowledge of credit. International Journal of Consumer Studies, Vol. 30 No. 4, 347-359.Leedy, P. D., & Ormrod, J. E. (2001). Practical Research: Planning and Design. London: Pearson.Livingstone, S., & Lunt, P. K. (1992). Predicting personal debt and debt repayment: psychological,social and economic determinants. Journal of Economic Psychology, Vol. 13 No. 1, 111-134.Malhotra, N. K. (2010). Marketing Research : An Applied Orientation sixth edition. PEARSON EDUCATION.Mannings, R. (1999). Credit Cards on Campus: Costs and Consequences of Student Debt. Consumer Federation of America, Washington, DC.Mansfield, P., & Pinto, M. (2008). Consumer vulnerability and credit card knowledge among developmentally disabled citizens. The Journal of Consumer Affairs, Vol. 42 No. 3, 425-438.Mantel, B. (2000). Why do Consumers Pay Bills Electronically? An Empirical Analysis. Economic Perspectives Federal Reserve Bank of Chicago, 4th Quarter, 32-47.Margianto, H. (2014, August 30). Kompas. Retrieved from Kompas.com: https://ekonomi.kompas.com/read/2014/08/30/204444826/.Cashless.Society.Ketika.Uang.Fisik.Hilang.dari.Dompet.AndaMaurya, U. K., & Mishra, P. (2012). What is a Brand? A Perspective on Brand Meaning. European Journal of Business and Management.McCoy, S., Everard, A., Polak, P., & Galletta, D. F. (2008). An experimental study of antecedents and consequences of online ad intrusiveness. Journal of Human Computer Interaction, 672-699.Merriam-Webster. (2018). Merriam-Webster: Questionnaire. Retrieved from Merriam-Webster:: https://www.merriam-webster.com/dictionary/questionnaireMester, L. (2003). Changes in the Use of Electronic Means of Payment: 1995-2001. Federal Reserve Bank of Philadelphia Business Review, Q3, 18-20.Moore, R. (2004). Credit card knowledge, attitudes, and practices of college students. Dissertation, Texas Tech University, Lubbock, TX.Moschis, G. P., & Moore, R. L. (1984). Anticipatory consumer socialization. Journal of Academy of Marketing Science, Vol. 12 No. 4, 109-123.Najmi, M., Atefi, Y., & Mirbagheri, S. A. (2012). Attitude toward Brand: An Integrative Look at Mediators and Moderators. Academy of Marketing Studies Journal, 111-133.Norvilitis, J. M., & Santa Maria, P. (2002). Credit card debt on college campuses: causes, consequences,and solutions. College Student Journal, Vol. 36 No. 3, 357-364.Norvilitis, J. M., Merwin, M. M., Osberg, T. M., Roehling, P. V., Young, P., & Kamas, M. M. (2006). Personality factors, money attitudes, financial knowledge, and credit-card debt in college. Journal of Applied Social Psychology, Vol. 36 No. 6, 1395-1413.Norvilitis, J. M., Merwin, M. M., Osberg, T. M., Roehling, P. V., Young, P., & Kamas, M. M. (2006). Personality factors, money attitudes, financial knowledge, and credit-card debt in college students. Journal of Applied Social Psychology Vol. 36 No. 6, 1395-1413.Norvilitis, J., & MacLean, M. (2010). The role of parents in college students’ financial behaviors and attitudes. Journal of Economic Psychology, Vol. 31 No. 1, 55-63.Omar, N. A., Rahim, R. A., Che Wel, C. A., & Alam, S. S. (2014). Compulsive buying and credit cardmisuse among credit card holders: the roles of self-esteem, materialism, impulsive buying and budget constraint. Intangible Capital, Vol. 10 No. 1, 52-74.O'Sullivan, A., & Sheffrin, S. M. (2003). Economics: Principles in action (Textbook). Upper Saddle River, New Jersey: Pearson Prentice Hall.Palan, K. M., Morrow, P. C., Trapp, A., & Blackburn, V. (2011). Compulsive buying behavior in college students: the mediating role of credit card misuse. Journal of Marketing Theory and Practice, 81-96.Palmer, T. S., Pinto, M. B., & Parente, D. H. (2001). “College students’ credit card debt and the role of parental involvement: implications for public policy. Journal of Public Policy & Marketing, Vol. 20 No. 1, 105-113.Pechmann, C., Moore, E., Andreasen, A., Connel, P., Freeman, D., Gardner, M., . . . Soster, R. (2011). Navigating the central tensions in research on at-risk consumers: challenges and opportunities. Journal of Public Policy & Marketing, Vol. 30 No. 1, 23-30.Perry, V., & Morris, M. (2005). Who is in control? The role of self-perception, knowledge, and income in explaining consumer financial behavior. The Journal of Consumer Affairs, Vol. 39 No. 2, 299-313.Pindyck, R., & Rubinfeld, D. (2004). Microeconomics, 6th ed. Upper Saddle River, NJ: Prentice-Hall.Pinto, B., Parente, D., & Palmer, T. (2000). “Materialism and credit card use by college students . Psychological Reports, Vol. 86 No. 2, 643-652.Pinto, M., Parente, D., & Mansfield, P. (2005). Information learned from socialization agents: its relationship to credit card use. Family and Consumer Sciences Research Journal, Vol. 33 No. 4, 357-367.Pirog, S., & Roberts, J. A. (2007). Personality and credit card misuse among college students: the mediating role of impulsiveness. The Journal of Marketing Theory and Practice, Vol. 15 No. 1, 65-77.Prelec, D., & Simester, D. (2001). Always leave home without it: a further investigation of the credit-card effect on willingness to pay. Marketing Letters, Vol. 12 No. 1, 5-12.Richins, M. (2011). Materialism, transformation expectations, and spending: implications for credit use. Journal of Public Policy & Marketing, Vol. 30 No. 2, 141-156.Richsen, H. (2015). Validity. Retrieved from Linguistic: http://linguistics.byu.edu/faculty/henrichsenl/ResearchMethods/RM_2_18.htmlRidwan. (2004). Metode dan Teknik Menyusun Tesis. Bandung: Alfabeta.Robb, C. A. (2011). Financial knowledge and credit card behavior of college students. Journal of Family and Economic Issues, Vol. 32 No. 4, 690-698.Robb, C. A., Moody, B., & Abdel-Ghany, M. (2012). College student persistence to degree: the burden of debt. Journal of College Student Retention, Vol. 13 No. 4, 431-456.Robb, C., & Sharpe, D. (2009). Effect of personal financial knowledge on college students’ credit card behavior. Journal of Financial Counseling and Planning, Vol. 20 No. 1, 25-43.Roberts, J. A., & Tanner, J. F. (2000). Compulsive buying and risky behavior among adolescents. Psychological Reports Vol. 86 No. 3, 763-770.Rysman, M. (2007). An Empirical Analysis of Payment Card Usage. Journal of Industrial Economics, 55, 1-36.SallieMae. (2012). “How undergraduate students use credit cards: Sallie Mae’s national study of usage rates and trends 2009. 1-19.Santos, D., Mendes-Da-Silva, W., Flores, E., & Norvilitis, J. (2016). Predictors of credit card use and perceived financial well-being in female college students: a Brazil-United States comparative study. International Journal of Consumer Studies, Vol. 40 No. 2, 133-142.Shields, P., & Rangarajan, N. (2013). A Playbook for Research Methods: Integrating Conceptual Frameworks and Project Management. New Forums Press.Shim, S., Barber, B., Card, N., Xiao, J., & Serido, J. (2010). Financial socialization of first-year college students: the roles of parents, work, and education. Journal of Youth and Adolescence, Vol. 39 No. 12, 1457-1470.Sidoti, P. M., & Devasagayam, R. ((2010)). Credit cards and college students: effect of materialism and risk attitude on misuse. The Marketing Management Journal, Vol. 20 No. 2, 64-79.Simkovic, M. (2008). The Effect of BAPCPA on Credit Card Industry Profits and Prices. American Bankruptcy Law Journal, Vol. 83, No. 1, 2009.Soman, D. (2001). Effects of payment mechanism on spending behavior: the role of rehearsal and immediacy of payments. Journal of Consumer Research, Vol. 27 No. 4, 460-474.Soman, D. (2003). The effect of payment transparency on consumption: the effects of payment transparency on consumption: quasi-experiments from the field. Marketing Letters Vol. 14 No. 3, 173-183.Soman, D., & Cheema, A. (2002). The effect of credit on spending decisions: the role of credit limit and credibility. Marketing Science, Vol. 21 No. 1, 32-53.Soman, D., Cheema, A., & Chan, E. (2011). Understanding consumer psychology to avoid abuse of credit cards. Transformative Consumer Research for Personal and Collective Well-Being, 423-444.Sotiropoulos, V., & d’Astous, A. (2013). Attitudinal, self-efficacy, and social norms determinants of young consumers’ propensity to overspend on credit cards. Journal of Consumer Policy, Vol. 36 No.2, 179-196.Stavins, J. (2001). Effect of Consumer Characteristics on the Use of Payment Instruments. New England Economic Review 3, 19-31.Szmigin, I., & O’Loughlin, D. (2010). Students and the consumer credit market: towards a social policy agenda. Social Policy & Administration, Vol. 44 No. 5, 598-619.Szmigin, I., & O’Loughlin, D. (2010). Students and the consumer credit market: towards a social policy agenda. Social Policy & Administration, Vol. 44 No. 5, 598-619.TechTarget. (2018). Definition: Hypothesis. Retrieved from TechTarget: https://whatis.techtarget.com/definition/hypothesisTeoh, W. M.-Y., Chong, S.-C., & Yong, S. (2013). Exploring the factors influencing credit card spending behavior among Malaysians. International Journal of Bank Marketing Vol. 31 No. 6, 481-500.Wang, J., & Xiao, J. (2009). Buying behavior, social support and credit card indebtedness of college students. International Journal of Consumer Studies, Vol. 33 No. 1, 2-10.Wang, L., Lu, W., & Malhotra, N. K. (2011). Demographics, attitude, personality and credit card features correlate with credit card debt: a view from China. Journal of Economic Psychology, Vol. 32 No. 1, 179-193.Ward, S. (1974). Consumer socialization. Journal of Consumer Research, Vol. 1 No. 2, 1-14.Wardani, P. (2012). Faktor-faktor yang Mempengaruhi Luas Pengungkapan Sukarela. Surabaya: Fakultas Bisnis Universitas Katolik Widya Mandala.Warwick, J., & Mansfield, P. M. (2000). Credit card consumers: college students’ knowledge and attitude. Journal of Consumer Marketing Vol. 17 No. 7, 617-626.Wikipedia. (2015). Convergent Validity. Retrieved from Wikipedia: https://en.wikipedia.org/wiki/Convergent_validityWikipedia. (2016). Wikipedia. Retrieved from Discriminant Validity: https://en.wikipedia.org/wiki/Discriminant_validityWilliams, C. (2007). Research Methods. Journal of Business & Economics Research.Wood, K. (2010). Credit card accountability, responsibility and disclosure act of 2009: protecting young consumers or impinging on their financial freedom. Brooklyn Journal of Corporate, Financial & Commercial Law, Vol. 5 No. 2010, 159-183.Xiao, J. J., Tang, C., Serido, J., & Shim, S. (2011). Antecedents and consequences of risky credit behavior among college students: application and extension of the theory of planned behavior. Journal of Public Policy & Marketing, Vol. 30 No. 2, 239-245.